Iron deficiency anemia and eating habits and their association with the health profile of riverside children in the communities of Combu island, Pará / Brazil (Research, Society and Development, 2020)
The present study aimed to characterize the occurrence of iron deficiency anemia in the infant population bordering Ilha do Combu, from zero (0) to 12 years of age, identifying the prevalence and possible interference of children's eating habits in this clinical health condition. The criteria were assessed by three anthropometric measures: weight, age and height, using the WHO / MS anthropometric reference, and the diagnosis of anemia, which was carried out in two stages: 1) collection of digital pulp hemoglobin, 2) by determining hemoglobin concentration, serum iron concentration and serum ferritin. This is a qualitative and quantitative study of an epidemiological descriptive nature, carried out in the Family Health Strategy (FHS) in Ilha do Combu with the igarapé Combu and igarapé Piriquitaquara communities, carried out from October 2018 to February 2019, and included 153 children. The prevalence of iron deficiency anemia was found to be only 10%, with anemic classification between mild (Hb = 9.5g / dl) and moderate (Hb = 7.2g / dl), and no case of severe anemia (Hb